A Moderated Mediation Model of Wellbeing and Competitive Anxiety in Male Marathon Runners - Jaenes, Jose C.; Alarcón, David; Trujillo, Manuel; Méndez-Sánchez, María del Pilar; León-Guereño, Patxi; Wilczyńska, Dominika (Frontiers in Psychology, 2022)
Running marathons is an increasingly popular activity with an ever-increasing number of events and participants. Many participants declare that they pursue a variety of goals by running: the maintenance of good health, the development of strength and improvement of fitness, the management of emotions and the achievement of resilience and psychological wellbeing. The research has examined marathon running, like many other sports, and has studied various factors that reduce athletic performance, such as the experience of anxiety, and factors that enhance such performance, such as an increase in general well-being. This paper reports the results of a study of the experience of competitive anxiety among 238 male marathon runners who participated in Seville’s (Spain) 26th Marathon race on February 23rd, 2020, and investigates the relationship between anxiety and key dimensions of well-being as measured by the Spanish-adapted 20-item Psychological Wellbeing (PWB) Scale (Diaz et al. 2000). We hypothesized that participating athletes who rated high on the dimensions of psychological well-being would experience lower levels of competitive anxiety with respect to this race. We also proposed that psychological well-being would function as a mediating factor with respect to the experience of anxiety. The results show, as hypothesized, that marathon running enhances well-being and reduces anxiety. The data showed significant negative correlations between four of five well-being dimensions and the three types of anxiety measured: somatic anxiety, worry, and concentration-impairing anxiety (ps < .01). Other findings supported our hypothesis that well-being, as measured, functions as a mediating factor for the moderation of competitive anxiety. Generalization of these findings is limited by the fact that the low number of female participants recruited did not permit valid statistical analyses in this respect. It is known that both anxiety and well-being are subject to variation by gender. The future inclusion of male and female subjects in equivalent studies will undoubtedly add valuable information concerning the dynamics of anxiety and well-being. The implications of these findings and the limitations of the study will be discussed.